New approach of (G′G)-expansion method and new approach of generalized (G′G)-expansion method for nonlinear evolution equation - Naher, Hasibun (© 2013 AIP Advances, 2016)
This article was published inAIP Advances [ © 2013 Copyright Author(s) ] and the definite version is available at : http://dx.doi.org/10.1063/1.4794947 The Journal's website is at: http://scitation.aip.org/content/aip/journal/adva/3/3/10.1063/1.4794947